2022
DOI: 10.1055/s-0042-1754317
|View full text |Cite
|
Sign up to set email alerts
|

Stent-Graft Migration Post-Endovascular Repair of Thoracic Aorta: A Retrospective Cohort Study

Abstract: Background Migration of the stent-graft post-thoracic endovascular aortic repair (TEVAR) is not uncommon; however, it is sparsely reported. The objective of this study was to assess the incidence, risk factors, and complications of stent-graft migration post-TEVAR. Materials and Methods Thirty-one patients who underwent TEVAR were retrospectively analyzed. The demographic, anatomical, and procedure-related factors were assessed. The measurements were done along the greater curvature of aorta around t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…A previous study showed that the incidence of thoracic SG migration was 7.3–19.3%. 4 , 5 Stent graft migration is likely to occur at the proximal landing zone and also the overlapping and distal landing zones. 4 Previous studies have reported that the risk factors or predictors of SG migration after TEVAR include aortic elongation, the proximal fixation length, and thoracic aortic aneurysm (TAA).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study showed that the incidence of thoracic SG migration was 7.3–19.3%. 4 , 5 Stent graft migration is likely to occur at the proximal landing zone and also the overlapping and distal landing zones. 4 Previous studies have reported that the risk factors or predictors of SG migration after TEVAR include aortic elongation, the proximal fixation length, and thoracic aortic aneurysm (TAA).…”
Section: Discussionmentioning
confidence: 99%
“… 4 Previous studies have reported that the risk factors or predictors of SG migration after TEVAR include aortic elongation, the proximal fixation length, and thoracic aortic aneurysm (TAA). 4 , 5 In terms of abdominal endovascular aortic repair, proximal neck angulation >60° increases the risk of device migration and endoleak. 6 In this case, the proximal neck length was sufficient at approximately 30 mm ( Fig.…”
Section: Discussionmentioning
confidence: 99%